Neuroprotective Effect of Dexmedetomidine on Hyperoxia-Induced Toxicity in the Neonatal Rat Brain. (13th January 2015) - Sifringer, Marco; von Haefen, Clarissa; Krain, Maria; Paeschke, Nadine; Bendix, Ivo; Bührer, Christoph; Spies, Claudia D.; Endesfelder, Stefanie
Abstract : Dexmedetomidine is a highly selective agonist of α 2-receptors with sedative, anxiolytic, analgesic, and anesthetic properties. Neuroprotective effects of dexmedetomidine have been reported in various brain injury models. In the present study, we investigated the effects of dexmedetomidine on neurodegeneration, oxidative stress markers, and inflammation following the induction of hyperoxia in neonatal rats. Six-day-old Wistar rats received different concentrations of dexmedetomidine (1, 5, or 10  µ g/kg bodyweight) and were exposed to 80% oxygen for 24 h. Sex-matched littermates kept in room air and injected with normal saline or dexmedetomidine served as controls. Dexmedetomidine pretreatment significantly reduced hyperoxia-induced neurodegeneration in different brain regions of the neonatal rat. In addition, dexmedetomidine restored the reduced/oxidized glutathione ratio and attenuated the levels of malondialdehyde, a marker of lipid peroxidation, after exposure to high oxygen concentration. Moreover, administration of dexmedetomidine induced downregulation of IL-1 β on mRNA and protein level in the developing rat brain. Dexmedetomidine provides protections against toxic oxygen induced neonatal brain injury which is likely associated with oxidative stress signaling and inflammatory cytokines. Our results suggest that dexmedetomidine may have a therapeutic potential since oxygen administration to neonates is sometimes inevitable.